2017
DOI: 10.1242/jcs.191213
|View full text |Cite
|
Sign up to set email alerts
|

Multiple routes of endocytic internalization of PDGFRβ contribute to PDGF-induced STAT3 signaling

Abstract: Platelet-derived growth factor receptor β (PDGFRβ) is a receptor tyrosine kinase which upon activation by PDGF-BB stimulates cell proliferation, migration and angiogenesis. Ligand binding induces intracellular signaling cascades but also internalization of the receptor, eventually resulting in its lysosomal degradation. However, endocytic trafficking of receptors often modulates their downstream signaling. We previously reported that internalization of PDGFRβ occurs via dynamin-dependent and -independent pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 56 publications
(85 reference statements)
2
49
0
Order By: Relevance
“…Another possible explanation for the reduced protein levels of PDGFR-β in WT mice could be that activation of the PDGFR-β pathway led to internalization of PDGFR-β and thereby reduction in the total PDGFR-β protein. We and others have previously shown that stimulation of PDGFR-β results in decreased surface expression and internalization, which are associated with increased phosphorylation of the receptor (3034). The increased activation of PDGFR-β as indicated by the increased ratio of pPDGFR-β to total PDGFR-β in WT mice might facilitate pericyte detachment from the vessels and increase the density of parenchymal pericytes.…”
Section: Discussionmentioning
confidence: 94%
“…Another possible explanation for the reduced protein levels of PDGFR-β in WT mice could be that activation of the PDGFR-β pathway led to internalization of PDGFR-β and thereby reduction in the total PDGFR-β protein. We and others have previously shown that stimulation of PDGFR-β results in decreased surface expression and internalization, which are associated with increased phosphorylation of the receptor (3034). The increased activation of PDGFR-β as indicated by the increased ratio of pPDGFR-β to total PDGFR-β in WT mice might facilitate pericyte detachment from the vessels and increase the density of parenchymal pericytes.…”
Section: Discussionmentioning
confidence: 94%
“…Protein A Sepharose and Glutathione Sepharose resins were from GE Healthcare (Piscataway, NJ, USA). siRNA was from Thermo Fisher Scientific or from GE Dharmacon (Lafayette, CO, USA) as described previously [47].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were transfected with siRNA against endocytic proteins with Lipofectamine RNAiMAX (Thermo Fisher Scientific), as described previously [47]. U2OS‐R1 cells were treated for 3 days in 5% CO 2 atmosphere at 37 °C with 20 n m Ambion Silencer Select siRNA against clathrin heavy chain (CHC_1 ‐ #s475, CHC_2‐ #s477), a μ2 subunit of the AP2 complex (AP2μ2) (AP2M1_1 ‐ #s3112, AP2M1_2 ‐ #s3113), dynamin‐2 (DNM2_1 ‐ #s4212, DNM2_2 ‐ #s4213), galectin‐3 (GAL3_1 ‐ #s8148, GAL3_2‐ #s8149), CD44 (CD44_1‐ #s2681), ROCK1 (ROCK1_1 ‐ #s12097, ROCK1_2 ‐#s12098), and ROCK2 (ROCK2_1 ‐ #s18161, ROCK2_2‐ #s18162) were from Thermo Fisher Scientific.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, PDGFR-β is known to induce STAT3 phosphorylation, and activated STAT3 leads to cell transformation [47,48]. Consequently, elevated STAT3 signaling inhibits apoptosis and supports cancer survival, producing a phenotype similar to chemo-resistance [49].…”
Section: Discussionmentioning
confidence: 99%